Vibrational study of S(-) and R(+) forms of analgesic camphor combining DFT calculations with normal internal coordinates and SQMFF methodology - Ruiz Hidalgo, José (2020)
B3LYP/6-311++G** calculations were performed to study structures and vibrationalproperties of Cis S(-) and R(+) forms of camphor. Comparisons between calculatedgeometrical parameters of both forms of Camphor in gas phase and aqueous solutionshow very good concordances with the experimental ones corresponding to (+)-3-bromocamphor. NBO calculations predict only →*, →* and n→* interactions althougth the expected n→* transitions due to ketone groups C=O were no predicted. Gap and electrophilicity index (ω) values of both forms of camphor are close to the valueobserved in antiviral thymidine. Such observations could be explained by the proximitiesbetween the acceptor groups H bonds (C=O) and the CH3 groups present in both camphorand thymidine species. Reasonable concordances were found among the predicted 1H- and 13C-NMR, UV-visible, ECD, IR and Raman spectra with the corresponding experimental ones. Complete vibrational assignments and scaled force constants for both forms camphor are reported for first time.